2018
DOI: 10.18632/oncotarget.24857
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNAs species in the blood of small cell and non-small cell lung cancer patients

Abstract: Lung cancer is a devastating disease with overall bleak prognosis. Current methods to diagnose lung cancer are rather invasive and are inadequate to detect the disease at an early stage when treatment is likely to be most effective. In this study, a shotgun sequencing approach was used to study the microRNA (miRNA) cargo of serum-derived exosomes of small cell lung cancer (SCLC) (n=9) and non-small cell lung cancer (NSCLC) (n=11) patients, and healthy controls (n=10). The study has identified 17 miRNA species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…On the other hand, in SCLC, Nishikawa et al showed that miR-375 was significantly increased in SCLC cell lines as opposed to those of different histologic types when they examined the miRNA expression profiles on lung cell lines [182]. Moreover, a recent cohort study has identified 13 miRNAs able to accurately differentiate between SCLC and NSCLC patients, 3 of which, namely hsa-miR-331-5p, hsa-miR-451a and hsa-miR-363-3p, reaching sensitivity and specificity of 100% [183].…”
Section: Mirnas In Distinguishing Cancer Subtypesmentioning
confidence: 99%
“…On the other hand, in SCLC, Nishikawa et al showed that miR-375 was significantly increased in SCLC cell lines as opposed to those of different histologic types when they examined the miRNA expression profiles on lung cell lines [182]. Moreover, a recent cohort study has identified 13 miRNAs able to accurately differentiate between SCLC and NSCLC patients, 3 of which, namely hsa-miR-331-5p, hsa-miR-451a and hsa-miR-363-3p, reaching sensitivity and specificity of 100% [183].…”
Section: Mirnas In Distinguishing Cancer Subtypesmentioning
confidence: 99%
“…Another study identified 17 miRNA species in the exosomes of the blood that are differentially expressed in cancer (both NSCLC and SCLC) and controls (27). The potential use of ctDNA for early detection of other cancers has also been reported (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…When the tissue obtained is sufficient for a histopathological analysis, a definitive diagnosis is more likely. However, even if a sufficient biopsy can be obtained, it is an unreliable method in cases of heterogeneous and continuously evolving tumors, because it increases the patient's risk and discomfort when collecting repetitive samples [21,22].…”
Section: Lung Cancer Diagnosismentioning
confidence: 99%